Research progress of microcystin-LR toxicity to the intestine, liver, and kidney and its mechanism - Yaqi Wang; Xiaodie Zhou; Yue Yang; Jun Liu; Fei Yang (Environment International)
Global warming and eutrophication of water bodies have exacerbated the occurrence of cyanobacterial blooms in recent years. Microcystin-LR (MC-LR) produced by cyanobacterial blooms is present in water bodies. Humans and livestock are at significant risk of exposure to MC-LR through drinking water, consuming contaminated food, or inhalation of aerosols containing MC-LR. This article systematically summarizes the formation, fate, and distribution of MC-LR in the body, and explores its toxic effects and mechanisms on the multiple organs containing intestines, liver and kidneys. The study comparatively elucidated MC-LR exerted toxicity including abnormal cell proliferation, inflammation and fibrosis primarily through the following classical mechanisms: (1) inhibiting protein phosphatase 2A (PP2A), thereby affecting signaling pathways such as JNK/P38, MAPK/ERK, and PI3K/AKT; (2) inducing oxidative stress. Additionally, we summarized new mechanisms: (1) MC-LR affects mitophagy or induces mitochondrial structure damage; (2) MC-LR can induce intestinal microbiota dysbiosis, which in turn causes liver and kidney damage via the “gut-liver” axis and “gut-kidney” axis. This study presents the first systematic analysis of the multi-organ toxic effects induced by MC-LR, elucidates potential specific and shared toxic mechanistic pathways and proposes some future research directions to mitigate MC-LR-associated health risks.